EFFECTIVENESS OF EDUCATION ON REPRODUCTIVE HEALTH IN IMPROVING KNOWLEDGE AND ATTITUDES TOWARD CHILD MARRIAGE PREVENTION AT THE ADOLESCENT POSYANDU IN TRUCUK - Alfa Khamdia; Sri Mulyani; Siti Patonah (PT. Radja Intercontinental Publishing, 2026)
Child marriage remains a significant issue in Indonesia, including in Trucuk District, Bojonegoro Regency. One preventive effort that can be carried out is through reproductive health education at the Adolescent Posyandu. Health education aims to increase knowledge and shape better attitudes in preventing child marriage among adolescents. This study aims to analyze the effectiveness of reproductive health education in increasing knowledge and attitudes toward child marriage prevention at the Adolescent Posyandu in Trucuk. This study uses a quantitative method with a pre-experimental one-group pretest-posttest design. The research sample consists of adolescents actively participating in the Adolescent Posyandu in Trucuk, selected using purposive sampling techniques. Data were collected through questionnaires before and after the reproductive health education intervention. Data analysis was performed using a Wilcoxon Rank to assess changes before and after the education. The study results indicate a significant increase in adolescent knowledge and attitudes after receiving reproductive health education (p-value = 0.000 a <0.05). adolescents who previously had limited understanding of reproductive health and the risk of child marriage showed increased awareness and more positive attitudes after receiving the education. Reproductive health education has proven effective in enhancing knowledge and shaping better attitudes in preventing child marriage at the Adolescent Posyandu in Trucuk. This education program can serve as a recommended strategy for broader implementation to reduce child marriage rates in Indonesia.